2015
DOI: 10.1093/nar/gkv063
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric repeat-containing RNA/G-quadruplex-forming sequences cause genome-wide alteration of gene expression in human cancer cells in vivo

Abstract: Telomere erosion causes cell mortality, suggesting that longer telomeres enable more cell divisions. In telomerase-positive human cancer cells, however, telomeres are often kept shorter than those of surrounding normal tissues. Recently, we showed that cancer cell telomere elongation represses innate immune genes and promotes their differentiation in vivo. This implies that short telomeres contribute to cancer malignancy, but it is unclear how such genetic repression is caused by elongated telomeres. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 31 publications
1
61
0
1
Order By: Relevance
“…There have been fewer studies on the immunological effects of telomeric RNAs. However, a recent report showed that telomere RNA forming G-quadruplex structures can induce global changes in gene expression, including suppression of innate immune sensing genes (63).…”
Section: Discussionmentioning
confidence: 99%
“…There have been fewer studies on the immunological effects of telomeric RNAs. However, a recent report showed that telomere RNA forming G-quadruplex structures can induce global changes in gene expression, including suppression of innate immune sensing genes (63).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then incubated with a horseradish peroxidase (HRP)-conjugated anti-FLAG antibody (Abcam, Cambridge, UK) and the HRP substrate TMB (Roche, Mannheim, Germany), followed by measurement of absorbance at 450 nm. Circular dichroism spectra for confirmation of G-quadruplex formation were produced as described [23]. Sequences of oligonucleotides (oligos) used are as follows: KIT2 (G4 motif) 5â€Č-CGGGCGGGCGCGAGGGAGGGG-3â€Č; hTELO (G4 motif) 5â€Č-GG(TTAGGG) x4 TTAG-3â€Č; and control DNA (non-G4) 5â€Č-GGCATAGTGCGTGGGCG-3â€Č.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted, and GeneChip microarray analysis was performed as described [13]. The microarray data were deposited in the Gene Expression Omnibus database (www.ncbi.nlm.nih.gov/geo) under accession number GSE74304.…”
Section: Methodsmentioning
confidence: 99%